Pengaruh Permainan Kreatif Terhadap Perkembangan Sosial Anak Usia Dini Di Lingkungan Tk di Tomohon - Mario Erick Wantah; Threesje Tolukun; Azizah Nurfahmi Lupojo; Cahya Ananta Wollah; Dwi Setia Ningrum; Pratika Dwifarsi Durian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the influence of creative play on the social development of early childhood children in kindergarten settings in Tomohon. Using a quasi-experimental design and a mixed-methods approach, the research involved 40 children aged 4-6 years, divided into control and experimental groups. The results showed a significant improvement in social skills, including cooperation, communication, and conflict resolution, among children exposed to creative play. These findings align with the theory of learning through play, which emphasizes the importance of play in supporting holistic child development. This study highlights the need for integrating creative play into early childhood education to enhance social competencies.